The Formulation Of Herbal Mouthwash From Bangun-Bangun Leaves (Coleus amboinicus Lour) To Prevent The Occurrence Of Dental Plaque - Yenny Lisbet Siahaan; Renta Verawaty Siregar; Suryani Ompusunggu (Publisher Cv. Inara, 2021)
Herbs utilization spare new opportunities to handle dental health issues. Bangun-bangun leaves have chemical components which are strongly related to the prevention of the occurrence of dental plaque. The current research aimed to observe the effect of using mouthwash made from bangun-bangun leaves extract with the concentration of 40% and 80% towards the occurrence of dental plaque on the students of III A and III B classes in Private Madrasah Ibtidaiyah Annur Medan, North Sumatera. The research used quasi-experimental method through the Pre-Post Test with Control Group design. Analysis of this research was conducted initially through normality and homogeneity tests on the variants. If the variable is normally distributed then it means that the variable is not homogenous, leading to the testing of Difference between Two Means (t test) through two parties’ test of t’-test which was independent sample t-test. Through this research, researcher obtained t count of (57.20) > t table (1.987). Therefore, based on the basic of decision making through distinguishing t count and t table, then H0 was rejected and H1 was accepted. It means that there was difference on the treatment results between before and after using the 80% bangun-bangun leaves solution. Furthermore, the t count value (45.73) > t table (1.987), which based on the basis of decision making through distinguishing the t count and t table values was that H0 was rejected and H1 was accepted. It means that there was difference on the treatment results between the use of 40% and 80% of bangun-bangun leaves solution. It can be concluded that both of the uses of 40% and 80% of bangun-bangun leaves solution affected significantly on the prevention of students’ dental plaque occurrence.